Деякi достатнi умови збiжностi послiдовностей фiгурних наближень парного i непарного порядкiв для двовимiрних неперервних дробiв з дiйсними елементами - Антонова, Т. М.; Сусь, О. М. (Видавництво Національного університету "Львівська політехніка", 2009)
Розглядаються деякi достатнi умови збiжностi послiдовностей фiгурних наближень парного i непарного порядкiв для двовимiрних неперервних дробiв з дiйсними елементами. Встановлено ознаку збiжностi двовимiрних неперервних дробiв. The sufficient conditions of the convergence for sequences of figured approximants of even and odd orders for two-dimensional continued fractions with real elements are considered. The theorem of convergence for two-dimensional continued fractions with real elements is proved.
Certain in sufficient conditions of the convergence for sequences of figured approximants of even and odd orders for two-dimensional continued fractions with real elements
Keywords: неперервний дрiб; двовимiрний неперервний дрiб; фiгурний пiдхiдний дрiб; послiдовнiсть наближень; збiжнiсть; continued fraction; two-dimensional continued fraction; figured approximant; sequences of approximants; convergence